Indigenous-led camera-trap research on traditional territories informs conservation decisions for resource extraction - Jason T Fisher; Fabian Grey; Nelson Anderson; Josiah Sawan; Nicholas Anderson; Shauna-Lee Chai; Luke Nolan; Andrew Underwood; Julia Amerongen Maddison; Hugh W. Fuller; Sandra Frey (Canadian Science Publishing, 2021)
The resource extraction that powers global economies is often manifested in Indigenous Peoples' territories. Indigenous Peoples living on the land are careful observers of resulting biodiversity changes, and Indigenous-led research can provide evidence to inform conservation decisions. In the Nearctic western boreal forest, landscape change from forest harvesting and petroleum extraction is intensive and extensive. A First Nations community in the Canadian oil sands co-created camera-trap research to explore observations of presumptive species declines, seeking to identify the relative contributions of different industrial sectors to changes in mammal distributions. Camera data were analyzed via generalized linear models in a model-selection approach. Multiple forestry and petroleum extraction features positively and negatively affected boreal mammal species. Pipelines had the greatest negative effect size (for wolves), whereas well sites had a large positive effect size for multiple species, suggesting the energy sector as a target for co-management. Co-created research reveals spatial relationships of disturbance, prey, and predators on Indigenous traditional territories. It provides hypotheses, tests, and interpretations unique to outside perspectives; Indigenous participation in conservation management of their territories scales up to benefit global biodiversity conservation.